2017
DOI: 10.1111/grs.12145
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24‐epibrassinolide application on cool‐season turfgrass growth and quality under salt stress

Abstract: Brassinosteroids are steroidal phytohormones with a significant role in the amelioration of various stresses. The objective of this study was to determine the effect of foliar application of 24‐epibrassinolide (EBL) on growth and quality of perennial ryegrass (Lolium perenne L.) and tall fescue (Festuca arundinaceae Schreb.) grown under salt stress. The plants were grown under non saline or saline conditions (6 dS m−1), and were sprayed with 0.00 and 0.15 mg L−1 EBL. Salt stress significantly reduced the shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Additionally, application of exogenous polyamines such as spermidine could improve salt stress tolerance in Kentucky bluegrass and zoysiagrass [25,31]. Some hormones such as epibrassinolide, salicylic acid and glycinebetaine could enhance the salt tolerance of weeping alkaligrass (Puccinellia distans) tall fescue, perennial ryegrass and Kentucky bluegrass [38][39][40][41][42]. Ethylene is a negative regulating hormone in the plant stress response pathway, and its suppression can protect perennial ryegrass against salt stress [43].…”
Section: Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, application of exogenous polyamines such as spermidine could improve salt stress tolerance in Kentucky bluegrass and zoysiagrass [25,31]. Some hormones such as epibrassinolide, salicylic acid and glycinebetaine could enhance the salt tolerance of weeping alkaligrass (Puccinellia distans) tall fescue, perennial ryegrass and Kentucky bluegrass [38][39][40][41][42]. Ethylene is a negative regulating hormone in the plant stress response pathway, and its suppression can protect perennial ryegrass against salt stress [43].…”
Section: Salt Stressmentioning
confidence: 99%
“…To improve the stress tolerance of turfgrass, several methods were exploited. Generally, there are two main strategies: the application of molecules such as phytohormones, signal molecules, and other chemical compounds, or the improvement of the matrix with composts [8,41,69]. Relatively efficient and available exogenous molecules have not been reported yet.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Moreover, the root biomass was significantly increased under 50 and 100 mM NaCl treatments (Figure 1B,C). Differently, it has been reported that the growth of many glycophytes, especially traditional crops and turfgrasses in Poaceae such as wheat, rice, ryegrass and tall fescue, are inhibited by NaCl treatments lower than 100 mM [43][44][45]. Furthermore, although the leaf relative membrane permeability of buffalograss was significantly increased under the 200 mM NaCl treatment, the tissue biomass and tiller number were maintained at the same levels as those under the control condition (Figure 1), suggesting that buffalograss possesses a strong salt tolerance.…”
Section: Buffalograss Maintains High Photosynthetic Capacity Under Mo...mentioning
confidence: 96%
“…Considerable efforts have been made to enhance plant salt tolerance, including the use of signaling molecules as hydrogen peroxide (H2O2) (Gondim et al, 2012), abscisic acid (Li et al, 2010), compounds that release nitric oxide (NO) (Gadelha et al, 2017), polyamines (Kamiab et al, 2014), brassinosteroids (Sever Mutlu et al, 2017) and selenium (Jiang et al, 2017). These molecules were tested in order to evaluate their potential to mitigate the deleterious effects of salt stress in several crop species.…”
Section: Introductionmentioning
confidence: 99%